THE LINGUISTIC ANALYSIS OF THE GRAMMATICAL VARIABILITY - Allahverdiyeva Feride Mahammad (International Journal of Innovative Technologies in Social Science, 2022)
The actuality of the subject. Variability, and optionality is observed at all levels of the language as a universal feature of language means. One of the key features of contemporary linguistic research is the general typology of language means’ variability and focusing on issues such as functional specifications of various variants in the text. In contrast to other language levels, the problem of variability in syntax has been studied less. The complexity of the investigation of variability in the syntax field is conditioned by the dual nature of syntactic units, and their structure-content layout. The sentence as a syntactic unit changes the structural-content layout and functional aspect in the evolutionary process. Simple sentences the generally accepted communicative speech unit and generally accepted syntactic units have been widely studied in various aspects of modern linguistic studies and currently is being studied further. The simple sentence being a structural type of sentence had a long way to development in the modern English language as well as in other languages, and has come to the present situation having structural-semantic improvement through certain changes during the speech as a result of simplification in sentence models, the expression means in sentences. Until now, there is no comprehensive description of the variativity features of all syntactic models of simple sentences in the studies where the syntactic structure of the English language has been described. Still, structural-semantic features, variations emerged in the historical development process can be underlined as an important issue because of the controversial issues in the syntax with a simple sentence and this proves the relevance of the topic. All of these bring to the agenda the comparisons by analyzing the structure-semantic layout of the simple sentence in different periods of the English language, revealing the changes in the simple sentence models, sentence members, and their means of expression, word order, analyzing the causes of those changes as an actual lingvo-methodological issue. Many researchers (K.Abdullayev, S.Abdullayev, D.Yunusov, F.Veysalli, and others) have examined the problem of variativity in different types of sentences in Azerbaijani linguistics and have shown valuable works in this area. The term "variativity" is applied to describe the functionality of different language units in modern linguistics and during the discovery of its unobserved aspects. In recent decades, the concept of enhanced variativity in phonology has also contributed to extensive research in other areas of linguistics, including syntax.